Comparative Effects of Fenugreek and Moringa Extract Supplementation on Lactation Performance among Postpartum Breastfeeding Mothers: A Quasi-Experimental Study - Fatwa, Dyah Mayasari; Fitriyani, Elsi Aprilia; Febriani, Dian; Wardhani, Ayudya Sihangga (Journal of Applied Nursing and Health, 2026)
Background: Inadequate breast milk production remains a frequent reason for early supplementation and discontinuation of exclusive breastfeeding. Fenugreek (Trigonella foenum-graecum) and moringa (Moringa oleifera) are widely used as natural galactagogues; however, comparative evidence examining their relative effectiveness within the same postpartum population remains limited, particularly in community maternal health settings. Methods: A quantitative quasi-experimental study with a posttest-only control group design was conducted in 2025 in Karawang Regency, Indonesia, and reported in accordance with the TREND statement. A total of 45 postpartum breastfeeding mothers were allocated consecutively by facility to three groups: control (n = 15), fenugreek (n = 15), and moringa (n = 15). No pretest was conducted; therefore, baseline equivalence was not confirmed. The fenugreek group received 500 mg fenugreek seed extract twice daily for 7 days; the moringa group received 250 mg moringa leaf extract twice daily for 7 days — both doses based on published therapeutic evidence. Lactation performance was assessed on day 8 using a validated structured questionnaire and observation sheet (Cronbach’s α = 0.81; CVI = 0.89). Data were analysed using the Kruskal-Wallis test, followed by Mann-Whitney U post hoc comparisons with Bonferroni correction Results: Post-intervention lactation performance scores (mean ± SD) were 5.93 ± 1.03 (control), 8.93 ± 1.03 (fenugreek), and 9.73 ± 0.46 (moringa). The Kruskal-Wallis test showed a significant overall difference (H = 34.21, df = 2, p < 0.001, η² = 0.76). Pairwise comparisons showed significant differences for control vs. fenugreek (U = 4.50, Z = −4.68, p < 0.001, r = 0.85), control vs. moringa (U = 0.00, Z = −5.20, p < 0.001, r = 0.95), and fenugreek vs. moringa (U = 54.00, Z = −2.87, p = 0.004, r = 0.52). Conclusion: Both fenugreek and moringa supplementation significantly improved lactation performance compared with routine care. Moringa demonstrated statistically significantly higher performance than fenugreek. Randomised controlled trials with objective lactation indicators and confirmed baseline equivalence are needed to confirm these findings.